Pengaruh Faktor-Faktor Kualitas Pelayanan Terhadap Kepuasan Pelanggan Dan Implikasinya Terhadap Loyalitas Pelanggan Di Green Café & Resto Bandung - Imelda Megawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2017)
The purpose of this research is to determine and to overview the influence factors of service quality to customer satisfaction and its implications for customer loyalty. The object of research in this thesis is Green Café & Resto Bandung and the subject of this study is its customers which consists of 110 people. And the method of this research is hypothesis testing with path analysis. These results indicate that the variable tangible, empathy and customer satisfaction are at fairly high category, variable responsiveness, reliability and customer loyalty at the high category and variable assurance is at the low category. The influence factors of service quality on customer satisfaction are 79,7% and very high where the remaining 20,3% influenced by other factors. Total influence of tangible variables on customer satisfaction is 19%, empathy is 24.31%, responsiveness is 16,88%, reliability is 12,51% and assurance is 7,07%. The implications of service quality to loyalty is 86,1% and very high where the remaining 13,9 % influenced by other factors.